New GeneBank records of oil degrading bacteria isolated from polluted soil - Al-Kanany , Fadhil N.; Gmais , Satar A.; Jaafar, Raghad S.; AL-Badran, Omar A. (Mesopotamian Journal of Marine Sciences, 2022)
This work aimd at isolation and identification of the dominant bacteria present in the oil polluted soil, as well as deposited the new isolates in the GeneBank. Some chemical parameters of contaminated soil were measured. Ten isolates were identified and characterized depending on the biochemical tests, as well as genetic characteristics using 16S rRNA gene comparing with reference isolates in the GeneBank, and through the detection of base pair sequence variations. These new local isolates were deposited in a GenBank under a new accession numbers; (OK576381.1, OK662612, OK662613, OK662614, OK662615, OK662616, OK662617, OK662618, OK662619, OK662620). Mineral salts medium (MSM) broth supported with crude oil as only source of carbon was adopted to isolate the bacteria. Culture media were supported with the same chemical parameters as the soil samples in order to simulate the physiochemical criteria of the environment. The successfully identified and recorded genera related to the above accession numbers were; Pseudomonas aeruginosa, Acinetobacter radioresistens, Pseudomonas oryzihabitans, Aeromonas hydrophila, Pseudomonas putida, Micrococcus luteus, Pseudomonas guariconensis, Achromobacter xylosoxidans, Bacillus foraminis, Pseudomonas stutzeri.